Buying in and Checking out: Identity Development and Meaning Making in the Practice of Mathematics Homework - Mara Landers (Qualitative Research in Education, 2013)
This paper presents findings from an ethnographic study of the role and meaning of mathematics homework in the lives of middle school students. The study conceptualizes and examines homework as a social practice, with a focus on how students make meaning out of their experiences and the role of identity development in meaning making. Specifically, the study examines how middle school students come to value or reject mathematics homework. Case study analyses revealed two ways of characterizing students’ experiences with homework. Students who buy into homework develop aspects of their identities related to school, math and homework that support them in valuing homework. Students who check out develop aspects of their identities that support them in rejecting homework. The concepts of buying in and checking out have implications for theory development around motivation and identity and for school practices around homework.